The application of DEA-ZOGP for the optimization of supplier selection / Nur Rasyida Mohd Rashid ... [et al.] - Mohd Rashid, Nur Rasyida; Abdul Halim, Bushra; Ismail, Wan Rosmanira; Ahmad Sabri, Iman Nabila; Mohd Erffa, Nur Effatin Natasya; Azmi, Siti Nor Liyana (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
The supplier selection process is gaining more attention in the production industry. Selecting the right supplier is an essential issue in business as well as supply chain systems since most of the companies work with several suppliers. A company needs to choose the best supplier based on qualitative and quantitative aspects where choosing the right supplier is also perceived as a decision-making process that requires multiple objectives to be achieved. In this study, the Data Envelopment Analysis (DEA) and Zero One Goal Programming method (ZOGP) methods are applied to choose the best supplier for a food manufacturing company in terms of qualitative and quantitative measurement. The input for the DEA model is the raw materials price while the outputs criteria are delivery time, shipping amount and response in quality problems. Every supplier is given a rating by the company based on those output criteria through Likert Scale from 1-10. In contrast, the ZOGP method considers quantitative constraints such as demand, purchasing cost, supply delay time, delivery time and percentages of discount of the raw materials. The mathematical modelling in this study is being executed using LINGO software. Finally, this research determined the best suppliers where both methods showed consistent results. This indicates the feasibility of utilizing the DEA in assessing the efficiency of the suppliers as well as ZOGP for the optimization of supplier selection problems which involves multiple criteria and objectives.